2020
DOI: 10.15406/joentr.2020.12.00459
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and cognition: a discussion for audiologists and hearing healthcare professionals

Abstract: Among researchers, clinicians and patients, there is widespread and growing interest in the relationship between hearing and cognition. The Cognition in Hearing Special Interest Group (SIG) is part of the British Society of Audiology (BSA) and is uniquely positioned to explore the relationship between hearing loss, amplification and cognitive ability and cognitive decline. The multiplicity of emerging reports concerning hearing loss and cognition is increasing rapidly. In light of this vast growth, there is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This systematic review aims to investigate (a. There is no consensus on the role and impact of hearing loss on the deterioration of cognitive functioning 18 . The results of a study by Wong et al showed a significant decline in cognitive abilities in orientation in time and space, registration, complex commands, and repetition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic review aims to investigate (a. There is no consensus on the role and impact of hearing loss on the deterioration of cognitive functioning 18 . The results of a study by Wong et al showed a significant decline in cognitive abilities in orientation in time and space, registration, complex commands, and repetition.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such results indicate the complexity of the relationship between hearing and cognitive processes. The most common complaint among people with hearing impairment difficulty in understanding words in the presence of tinnitus 6,15,18 cognitive performance, social isolation, depression and hearing aid use was carried out with a subsample of the UK Biobank data set (n = 164,770. According to the research by Loughrey et al, hearing loss was less associated with the decline in executive functions and recall compared with long-term and semantic memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the impact of hearing loss on dementia, it has been well-documented that the most significant potentially modifiable risk factor for dementia is hearing loss (see Lin, Metter & O'Brien et al, 12 see Livingston et al, 7 see Beck, Bant & Clarke, 13 , see Beck, 14 and see Beck & Grisel 15 ) When hearing loss is diagnosed and managed early (through amplification, FM transmitters, digital remote microphones, telecoils and loop systems, assistive listening devices and more) long-term outcomes appear significantly improved, as compared to untreated hearing loss see Amieva et al, 16 Glick & Sharma, 17 and Jiang, Mishra, Shrestha et al 8 Older adults with dual sensory impairment (DSI; hearing and vision impairment) perceive even greater difficulty and worse outcomes than those with only vision or hearing loss. Across the USA, some 12% of the population has vision-only loss, approximately 13% have hearingonly loss, and about 8% have DSI Shakarchi, Assi, Ehrlich et al, 18 Nonetheless, a recent Scoping Review 19 reports despite a clear need, only limited outcomes-based information, regarding how and when optometrists work with dementia patients, is available.…”
Section: Introduction To Dementiamentioning
confidence: 99%
“…Regarding the impact of hearing loss on dementia, it has been well-documented that the most significant potentially modifiable risk factor for dementia is hearing loss (see Lin, Metter & O'Brien et al, 12 see Livingston et al, 7 see Beck, Bant & Clarke, 13 , see Beck, 14 and see Beck & Grisel 15 ) When hearing loss is diagnosed and managed early (through amplification, FM transmitters, digital remote microphones, telecoils and loop systems, assistive listening devices and more) long-term outcomes appear significantly improved, as compared to untreated hearing loss see Amieva et al, 16 Glick & Sharma, 17 and Jiang, Mishra, Shrestha et al 8 Older adults with dual sensory impairment (DSI; hearing and vision impairment) perceive even greater difficulty and worse outcomes than those with only vision or hearing loss. Across the USA, some 12% of the population has vision-only loss, approximately 13% have hearingonly loss, and about 8% have DSI Shakarchi, Assi, Ehrlich et al, 18 Nonetheless, a recent Scoping Review 19 reports despite a clear need, only limited outcomes-based information, regarding how and when optometrists work with dementia patients, is available.…”
Section: Introduction To Dementiamentioning
confidence: 99%